Evaluation of Hysteresis Models for Estimating the Characteristics of High Pressure Solenoid Valves for Mechanical Ventilation - Röhren Felix; Groß-Weege Ines; Leonhardt Steffen; Walter Marian (Current Directions in Biomedical Engineering, 2024)
The flow control of inspiratory valves for mechanical ventilation is a crucial element of the overall functionality as it mainly governs precision and safety. However, control tuning can be challenging as the widely used magnetic actuation principle comes with a hysteresis shaped characteristic. As a result, the production of ventilators is highly dependent on specific valves and therefore vulnerable if supply chains are interrupted as during the pandemic. An approach which is capable of providing a reliable control for a variety of standard solenoid valves would be beneficial. Therefore, this work examines different models of hysteresis and their precision when being applied to actual measurement data of high pressure solenoid valves as a foundation for a following model-based control approach which can be either feedback or feedforward. Regarding the precision, the Prandtl-Ishlinskii (PI) model outperformed alternative approaches (MAEbelow2.5 L/ min) for the chosen parameters which is why the model is described for fitting both the forward and inverse case.